Protease shaving of Mycobacterium tuberculosis facilitates vaccine antigen discovery and delivery of novel cargoes to the Mtb surface - Bianca A. Lepe; Christine R. Zheng; Owen K. Leddy; Benjamin L. Allsup; Sydney L. Solomon; Bryan D. Bryson (Microbiology Spectrum)
ABSTRACT Tuberculosis (TB) is the leading cause of infectious disease death and lacks a vaccine capable of protecting adults from pulmonary TB. The bacterial surface is a critical interface that shapes host-pathogen interactions. Several knowledge gaps persist in our understanding of Mycobacterium tuberculosis (Mtb)-host interactions that may be addressed by an improved understanding of the Mtb surface proteome, including the identification of novel vaccine targets as well as developing new approaches to interrogate host-pathogen interactions. Here, we sought to expand our understanding of the Mtb surface proteome in service of these knowledge gaps by adapting protease shaving protocols for multiplexed quantitative mass spectrometry. Pairing quantitative mass spectrometry with the construction of validation strains, we revealed several novel Mtb proteins on the Mtb surface largely derived from the PE/PPE class of Mtb proteins, including PPE18, a component of a leading Mtb vaccine candidate. We next exploited the localization of PPE18 to decorate the Mtb surface with heterologous proteins. Together, these studies reveal potential novel targets for new Mtb vaccines as well as facilitate new approaches to study difficult-to-study cellular compartments during bacterial growth and infection.IMPORTANCEThe surface of a bacterial pathogen is a critical interface between the bacterium and the immune system. A better understanding of this interface would facilitate the discovery of new vaccine targets, new virulence proteins, and enable new technologies that modify the bacterial surface. In this study, we established a multiplexed and quantitative biochemical strategy to study the surface of Mycobacterium tuberculosis (Mtb) and identified new vaccine targets. We furthermore established design rules for new technologies aimed at modifying the composition of the bacterial surface. Specifically, we achieved a biological milestone that has not been rigorously reported previously, which is the successful modification of the Mtb surface with a non-native protein.